2017
DOI: 10.5546/aap.2017.eng.453
|View full text |Cite
|
Sign up to set email alerts
|

Development of equations and proposed reference values to estimate body fat mass among Chilean children and adolescents

Abstract: Introduction. The assessment of body composition is relevant to establish nutritional status and identify potential health risks. Objective. a) To develop regression equations to predict fat mass (FM) using a dual-energy X-ray absorptiometry as reference method; b) to propose reference FM values based on chronological and biological age for Chilean children and adolescents. Methodology. Cross-sectional study in children and adolescents aged 5.0 to 18.9 years from the Maule Region (Chile). The sample was made u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This ensured a high precision in the equations proposed for both working groups. In addition, some previous studies have reported similar R 2 values and levels of agreement for samples of children and adolescents (Cameron et al, 2004; Cossio-Bolaños et al, 2017; Gómez-Campos et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…This ensured a high precision in the equations proposed for both working groups. In addition, some previous studies have reported similar R 2 values and levels of agreement for samples of children and adolescents (Cameron et al, 2004; Cossio-Bolaños et al, 2017; Gómez-Campos et al, 2017).…”
Section: Discussionsupporting
confidence: 61%
“…Of the 77 studies that reported sample size, 35 (45.5%) met the criterion of a sample size of ten participants per predictor variable [19, 26, 54, 55, 60-62, 64-66, 68, 69, 72-75, 78, 84, 85, 88-90, 92, 93, 96, 99, 100, 102-106, 109, 111, 112]. When considering 15 participants per predictor variable, 19 studies (24.4%) met this criterion [60,62,65,66,68,69,78,84,88,92,93,96,99,100,102,[104][105][106]111] (Table S4).…”
Section: Sample Size Of Reportsmentioning
confidence: 99%
“…An example of the divergent nomenclature in describing the same measurement is the use of suprailiac skinfold [56] and iliac crest skinfold [95], both of which refer to the skinfold thickness measured immediately above the iliac crest. As for different descriptions using the same nomenclature, the most extreme example is waist girth, which had nine different descriptions (Table S5), including measurements at the narrowest part of the torso [89], the midpoint between the lowest rib and the iliac crest [106], and the area of the greatest girth of the abdomen [113].…”
Section: Anthropometric Measurementsmentioning
confidence: 99%